2012
DOI: 10.1167/iovs.11-7744
|View full text |Cite
|
Sign up to set email alerts
|

Cultured Autologous Oral Mucosal Epithelial Cell Sheet (CAOMECS) Transplantation for the Treatment of Corneal Limbal Epithelial Stem Cell Deficiency

Abstract: CAOMECS is a well-tolerated and safe tissue-engineered product. These results suggest its efficacy for reconstructing the ocular surface in patients with total bilateral corneal LSCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
126
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(127 citation statements)
references
References 26 publications
1
126
0
Order By: Relevance
“…In the meantime, transplantation of in vitro cultured nonocular autologous oral mucosal epithelium has been used in patients with bilateral limbal cell deficiency, particularly for acute chemical burns. This procedure can give satisfactory results (Burillon et al, 2012;Chen et al, 2009) and provide adequate re-epithelialization and stabilization of the surface of the cornea if the cultured autologous thin sheets (with a few cells' worth of thickness) of oral mucosal epithelium are lifted with temperature sensitive cell sheet-lifting technology that preserves the cultured cell-cell junctions and an intact basement membrane for transplantation (Burillon et al, 2012). This method appears to prevent the vascularization and loss of corneal opacity previously associated with oral mucosal transplants that often had multiple epithelial layers of stratification and numerous mucosal cell structures (Chen et al, 2009).…”
Section: Limbal Stem Cellsmentioning
confidence: 85%
“…In the meantime, transplantation of in vitro cultured nonocular autologous oral mucosal epithelium has been used in patients with bilateral limbal cell deficiency, particularly for acute chemical burns. This procedure can give satisfactory results (Burillon et al, 2012;Chen et al, 2009) and provide adequate re-epithelialization and stabilization of the surface of the cornea if the cultured autologous thin sheets (with a few cells' worth of thickness) of oral mucosal epithelium are lifted with temperature sensitive cell sheet-lifting technology that preserves the cultured cell-cell junctions and an intact basement membrane for transplantation (Burillon et al, 2012). This method appears to prevent the vascularization and loss of corneal opacity previously associated with oral mucosal transplants that often had multiple epithelial layers of stratification and numerous mucosal cell structures (Chen et al, 2009).…”
Section: Limbal Stem Cellsmentioning
confidence: 85%
“…32 This problem may be circumvented by performing oral mucosal graft as a limbal surrogate 33 or ex vivo expansion of oral mucosal epithelial SCs, 34 especially for eyes where transplantation of allogeneic limbal SCs has failed or is not feasible. 35,36 …”
Section: Introductionmentioning
confidence: 99%
“…To find a proper substitutive cell source of LSCs, researchers also explored the potential of using oral mucosal epithelia and adult stem cells, such as hair follicle stem cells and marrow mesenchymal stem cells in LSCD cases and received several encouraging results. [11][12][13][14][15] However, all these sources have their own limitations. Because of the lack of antiangiogenic factors expression, the peripheral corneal neovascularization was observed frequently in COMET.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] However, all these sources have their own limitations. Some studies proved that cultivated oral mucosal epithelium transplantation (COMET) efficiently repaired the wound cornea in some LSCD cases in a few years, 14,15 but other long-term clinical observations showed that the peripheral corneal neovascularization could be frequently observed after COMET because of the lack of antiangiogenic factors expression, such as sFlt-1, TIMP-3, and TSP-1, in these transplanted cells. 16 And for patients with pemphigoid, Steven Johnson syndrome, and pemphigus, which could influence or destroy oral mucosa, COMET was also unsuitable.…”
Section: Introductionmentioning
confidence: 99%